(untitled) (Quinto Sol, 2019)
This article makes an analytic journey through the speeches made by Clarín newspaper about the forced disappearance of people between 1975 and 1978. It inquires about the possibilities and limits of media representation of the phenomenon, its effects on communication languages and tensions, ruptures and continuities between the figurations constructed over the years of greater extension and repressive intensity. The disappearances of journalists are analyzed, in particular, the case of the kidnapping and clandestine detention of Enrique Esteban, correspondent of the newspaper in Neuquén, and its impact on the thematization of the issue offered by the graphic medium. The study is proposed as a contribution to the understanding of the avatars of the semantic elaboration of the forced disappearance of people, their social representation and their socio-cultural processing in the mass graphic press during the last military dictatorship.